STUDY OF DIATOMS/AQUEOUS SOLUTION INTERFACE. I. ACID-BASE EQUILIBRIA AND SPECTROSCOPIC OBSERVATION OF FRESHWATER AND MARINE SPECIES - Gélabert A.; Pokrovsky O.S.; Schott J.; Boudou A.; Feurtet-Mazel A.; Mesmer-Dudons N.; Mielczarski J.; Mielczarski E.; Spalla O. (My University, 2004)
This work reports on a concerted study of diatom-water interfaces for two marine planktonic (Thalassiosira weissflogii= TW, Skeletonema costatum= SC) and two freshwater periphytic species (Achnanthidium minutissimum= AMIN, Navicula minima= NMIN). Proton surface adsorption was measured at 25°C, pH of 3 to 11 and ionic strength of 0.001 to 1.0 M via potentiometric titration using a limited residence time reactor. Electrophoretic mobility of living cells and their frustules was measured as a function of pH and ionic strength. Information on the chemical composition and molecular structure of diatoms surfaces was obtained using FT-IR (in situ attenuated total reflectance) and X-ray Photoelectron Spectroscopy (XPS). The surface area of living cells and their frustules in aqueous solutions was quantified using Small Angle X-ray Scattering Spectroscopy (SAXS).